The Influence Of Accounting Understanding, Education Level, And Business Size on The Quality of Financial Reports of UMKM In Surakarta City - Jesica Ayu Revila; Tituk Diah Widajantie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze and measure the effect of accounting understanding, education level, and business size on the quality of MSME financial reports in Surakarta City. The type of research used is quantitative research with primary data obtained through a questionnaire as a data collection tool. The population in this study were MSME actors in Surakarta City. Determination of the sample in this study using random sampling technique and obtained as many as 100 respondents. This research analysis technique uses the Partial Least Square (PLS) method and is tested using the SmartPLS 4.0 program. The results of this study indicate that accounting understanding has a positive and significant effect on the quality of MSME financial reports, the level of accounting education has a positive and significant effect on the quality of MSME financial reports, while business size has a positive and insignificant effect on the quality of MSME financial reports.